Monitoring and preliminary analysis of the natural responses recorded in a poorly accessible streambed spring located at a fluviokarstic gorge in Southern Spain - Martín-Rodríguez, José Francisco; Mudarra-Martínez, Matías; Andreo-Navarro, Bartolomé; De la Torre Martínez, Beatriz; Gil-Márquez, José Manuel; Martín-Arias, Javier; Nieto-López, José Manuel; Prieto Mera, Jorge Jesús; Rodríguez-Ruiz, María Dolores (My University, 2018)
The analysis of natural responses (hydrodynamic, hydrothermal and hydrochemical) of karst springs is a well-established approach to provide insights into the hydrogeological functioning of the aquifers that they drain. However, a suitable monitoring program of these responses are often difficult to launch in poorly accessible streambed springs, due to the mixing between surface water and groundwater, in addition to topographic impediments. This work describes the installation procedure of the measurement equipment and the preliminary hydrogeological dataset collected at the Charco del Moro spring (Southern Spain) during one year. This outlet emerges 5 m below water surface, at the bottom of a partially flooded 20 - 200 m deep and 2 km long gorge, eroded by the Guadiaro River streamflow. It is considered the largest discharge point in the region, draining groundwater from northern nearby carbonate outcrops, although its catchment area is not established yet. Continuous (hourly) monitoring of electrical conductivity, water temperature, turbidity and water level (discharge) reflects a high degree of heterogeneity in the duality of groundwater flow and storage dynamics, which is typical of karst conduit flow systems
Keywords: Karst; Monitoring; Karst (carbonate) aquifer; Natural responses; Functioning